Konstruksi Peran Ibu dalam Video Klip Bertaut - Frisca Mardinsah; Tangguh Okta Wibowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Mothers have many roles and mothers have also been widely constructed in various media products, including video klip “Bertaut”. this study aims to determine the construction of the mothers role described in the video klip Bertaut. This study uses the theory of social reality construction of mass media and a qualitative approach and uses the Semiotics method of Roland Barthes with his idea known as two orders of signification which includes denotation, connotation, and myth. The results of this study found that mothers played a role in filling in the void in their childern’s families who were intach as if they were whole again. This research also includes strengthening the role of mothers including mothers who care for their children, mothers who provide warmth, independent mothers, mothers (grandmothers) who care for their grandchildren, and mothers who provide peace.